Does Ownership Structure Affect Labor Decisions? - Hall, Curtis M. (The Accounting Review, 2016)
ABSTRACT This study examines how the incentives related to ownership structure influence labor cost management decisions in publicly traded and privately held organizations. I document that public banks have more elastic labor cost structures than private banks, which suggests that public bank managers prefer greater flexibility to remove labor resources when desired. Consistent with public banks facing greater financial reporting pressures, I find that they reduce labor costs to avoid earnings declines. However, I also find that the use of labor cost reductions to manage required regulatory capital is more pronounced in private banks. Consistent with the explanation that access to the equity markets allows public firms to sell equity in lieu of cutting costs, I find that the use of labor cost reductions to manage capital requirements is concentrated in the subsample of banks with lower equity issuances. These findings suggest that while public ownership induces financial reporting pressure, it may also alleviate regulatory pressure through greater ability to sell equity.